Backstepping control of two-mass system using induction motor drive fed by voltage source inverter with ideal control performance of stator current - Vo Thanh Ha; Le Trong Tan; Nguyen Duc Nam; Nguyen Phung Quang (Institute of Advanced Engineering and Science, 2019)
This paper describes the design and the simulation of a non-linear controller for two-mass system using induction motor basing on the backstepping method. The aim is to control the speed actual value of load motor matching with the speed reference load motor, moreover, electrical drive’s respone ensuring the “fast, accurate and small overshoot” and reducing the resonance oscillations for two-mass system using induction motor fed by voltage source inveter with ideally control performance of stator current. Backstepping controller uses the non-linear equations of an induction motor and the linear dynamical equations of two-mass system, the Lyapunov analysis and the errors between the real and the desired values. The controller has been implemented in both simulation and hardware-in-the-loop (HIL) real-time experiments using Typhoon HIL 402 system, when the drive system operates at a stable speed (rotor flux is constant) and greater than rated speed (field weakening area). The simulation and HIL results presented the correctness and effectiveness of the controller is proposed; furthermore, compared to PI method to see the response of the system clearly.